Fostering Habib's Engagement and Self-Regulation: A Case Study of a Child From a Refugee Family at Home and Preschool. (May 2015) - Haines, Shana J.; Summers, Jean Ann; Turnbull, Ann P.; Turnbull, H. Rutherford; Palmer, Susan
Developing children's self-regulation and engagement skills are primary goals of early childhood education. These skills are fostered in both home and preschool environments and can lead to improved educational outcomes. This qualitative case study investigated how a refugee family and Head Start teachers fostered the self-regulation and engagement skills of a 4-year-old boy at risk for disability. It found that adult expectations and practices related to protection, intervention, and affective response in his home environment differed greatly from those in his Head Start environment. His skills steadily improved in both settings during the 4-month study's duration. Implications include using a framework of the three domains—protection, intervention, and affective response—to guide future research.